Profil keterampilan berpikir kritis pada pembelajaran ipas di sekolah dasar Kota Surakarta - yulaikasari, ismunisa pingki; Saputri, Dwi Yuniasih (Universitas Sebelas Maret, 2026)
This study aims to assess the level of students’ critical thinking skills in science learning at elementary schools in Surakarta City. A descriptive qualitative approach was used, involving an experimental group and a control group. Data were collected through pretests and posttests. The validity of the instrument was evaluated based on specific indicators and tested on sample groups after expert validation. The results showed that students in the experimental group, who used augmented reality media combined with the Jigsaw learning model, demonstrated more effective improvements in critical thinking skills in science learning compared to the control group that used conventional methods. The N-gain scores in the experimental group ranged from medium to high categories, while those in the control group fell into the low to medium categories. This study recommends the implementation of innovative learning models to foster students’ critical thinking skills from an early age in basic education.